Measurement of Vessel Diameter During Angioplasty: Are We Accurately Performing This Task?. Issue 4 (22nd November 2013) - Salman, Loay; Vazquez‐Padron, Roberto I.; Castro, Hector; Monrroy, Mauricio; Abdelwahed, Yehia; Rizvi, Abid; Merrill, Donna; Asif, Arif
Abstract Vessel diameter is objectively measured by a lead ruler positioned in the fluoroscopic field and software calibration during angioplasty. We conducted a prospective study to evaluate the accuracy of lead ruler determination of vessel diameter. Chronic hemodialysis patients undergoing an angioplasty procedure were included in this study (n = 37). Vessel diameter was determined by calibrating the fluoroscopy machine to a ruler with lead markers placed in the fluoroscopic field. The same calibration was used to measure the fully effaced angioplasty balloon in its intravascular location. We compared the measured balloon diameter with the actual (manufacturer's) diameter. The approximate depth of the ruler from the measured vessel was also determined. Angioplasty balloons appeared 13.75–40.83% (mean 25.8% ± 7.015) smaller than the actual size of the balloon (p < 0.0001) when measured using a calibrated fluoroscopic machine. There was a tendency toward the fact that the bigger the distance between the ruler and the vessel (that contained the angioplasty balloon), the more likely the technique underestimated the size of the angioplasty balloon. Lead ruler method underestimates the diameter of the vessel. Recognizing such a discrepancy is important when determining the size of an angioplasty balloon or endovascular stent.